Energy beverages: Content and safety - Higgins, J. P.; Tuttle, T. D.; Higgins, C. L. (Mayo Clinic Proceedings, 2010)
Exercise is making a resurgence in many countries, given its benefits for fitness as well as prevention of obesity. This trend has spawned many supplements that purport to aid performance, muscle growth, and recovery. Initially, sports drinks were developed to provide electrolyte and carbohydrate replacement. Subsequently, energy beverages (EBs) containing stimulants and additives have appeared in most gyms and grocery stores and are being used increasingly by "weekend warriors" and those seeking an edge in an endurance event. Long-term exposure to the various components of EBs may result in significant alterations in the cardiovascular system, and the safety of EBs has not been fully established. For this review, we searched the MEDLINE and EMBASE databases from 1976 through May 2010, using the following keywords: energy beverage, energy drink, power drink, exercise, caffeine, red bull, bitter orange, glucose, ginseng, guarana, and taurine. Evidence regarding the effects of EBs is summarized, and practical recommendations are made to help in answering the patient who asks, "Is it safe for me to drink an energy beverage when I exercise?"